The Paradox of Realizing the Right to Education for Adjudicated Juveniles: Administrative Conflicts and the Efficacy of Inter-Institutional Agreements - Sidney Valery Picauly; Elsa Rina Maya Toule; Sherly Adam (SIGn Jurnal Hukum, 2026)
The fulfillment of the right to education for adjudicated juveniles constitutes an absolute mandate of restorative sentencing; however, its implementation experiences stagnation due to the conflict between the criminal law regime and the rigidity of the civil registration administrative system. This study aims to critique the conflict between administrative norms, evaluate the juridical efficacy of cooperative agreement documents, and analyze the legal implications arising from passive maladministration by partner institutions. This empirical legal research employs a qualitative, critical-analytical approach at the Ambon Class II JCF, involving five key informants selected via purposive sampling, and is supported by an analysis of eight institutional partnership instruments. The research findings demonstrate that the absence of National Identification Numbers, resulting from families’ sociological vulnerability, deprives adjudicated juveniles of their civil rights to obtain national diploma legality. This failure of legal protection is exacerbated by the cooperative documents’ weak binding capacity, which lacks public service sanction clauses. The structural weakness of these contractual instruments generates a sphere of impunity that facilitates passive maladministration manifesting as an omission by regional educational institutions. The relevant institution has been proven to have deferred the administration of equivalency examinations for three consecutive academic years without engaging hierarchical coordination to escalate the issue to the central ministry. Sociologically, the absence of graduation legality threatens the future of adjudicated juveniles within the formal labor market and potentially triggers recidivism. This study recommends affirmative interventions through cross-sectoral identity-recording services with population registration agencies, a complete overhaul of the construction of cooperative agreement clauses to establish enforceable public law instruments, and resolving government bureaucratic stagnation through the functions of Supervisory and Observational Judges.